2000
DOI: 10.1073/pnas.220392197
|View full text |Cite
|
Sign up to set email alerts
|

Discovering functional relationships between RNA expression and chemotherapeutic susceptibility using relevance networks

Abstract: In an effort to find gene regulatory networks and clusters of genes that affect cancer susceptibility to anticancer agents, we joined a database with baseline expression levels of 7,245 genes measured by using microarrays in 60 cancer cell lines, to a database with the amounts of 5,084 anticancer agents needed to inhibit growth of those same cell lines. Comprehensive pair-wise correlations were calculated between gene expression and measures of agent susceptibility. Associations weaker than a threshold strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
389
0
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 543 publications
(396 citation statements)
references
References 23 publications
3
389
0
4
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Previous efforts using this strategy have focused mainly on finding causes of drug resistance. [2][3][4]11,17,18 Gene expression signatures have also been used as surrogate markers of cellular states, for example, to identify agents that induce the differentiation of acute myeloid leukemia cells. 19 However, nearly all of these investigations have been based on single gene expression-drug response relationships, whereas complex interactions between a drug and highly interconnected biological networks may not be reflected solely by the state of any one gene.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Previous efforts using this strategy have focused mainly on finding causes of drug resistance. [2][3][4]11,17,18 Gene expression signatures have also been used as surrogate markers of cellular states, for example, to identify agents that induce the differentiation of acute myeloid leukemia cells. 19 However, nearly all of these investigations have been based on single gene expression-drug response relationships, whereas complex interactions between a drug and highly interconnected biological networks may not be reflected solely by the state of any one gene.…”
Section: Introductionmentioning
confidence: 99%
“…In [14] this benchmark was used to compare different algorithms, including Bayesian networks [15], ARACNe [26], and the context likelihood of relatedness (CLR) algorithm [14], a new method that extends the relevance networks class of algorithms [9]. They observed that CLR outperformed all other methods in prediction accuracy, and experimentally validated some predictions.…”
Section: Reconstruction Of Gene Regulatory Networkmentioning
confidence: 99%
“…Another rationale for de novo inference is to connect genes or proteins that are similar to each other in some sense [25,30], For example, co-expression networks, or the detection of similar phylogenetic profiles are popular ways to infer "functional relationships" between proteins, although the meaning of the resulting edges has no clear biological justification [36]. Similarly, some authors have attempted to predict gene regulatory networks by detecting large mutual information between expression levels of a TF and the genes it regulates [9,14].…”
Section: Introductionmentioning
confidence: 99%
“…44 A second use for the oligonucleotide microarray is that of biopharmacology, where anticancer agent efficacy can be correlated to gene expression in tissue. 45,46 Complimentary to these novel genomic initiatives is proteomics, the study of expressed proteins in tissue and cell types. 47 Both proteomic and other tissue microarray studies are enhanced by the use of laser capture microdissection which enables isolation of critical neoplastic cells.…”
Section: Molecular Adjuncts To Diagnosis: the Microarraymentioning
confidence: 99%